Chemical recycling of polyenaminones by transamination reaction via amino–enaminone polymerisation/depolymerisation. (December 2019) - Zupanc, Anže; Kotnik, Tomaž; Štanfel, Urša; Brodnik Žugelj, Helena; Kristl, Anja; Ručigaj, Aleš; Matoh, Lev; Pahovnik, David; Grošelj, Uroš; Opatz, Till; Požgan, Franc; Štefane, Bogdan; et al.
Graphical abstract: Highlights: Mild reaction conditions, step-wise polymerisation, M w 3.000 Da. Facile depolymerisation with dimethylamine, closed-loop recycling. Porous microstructure, insoluble, film forming and UV-shileding properties. Tunability of polymer structure. Broad substrate availability, combinatorial synthesis feasible. Abstract: Novel oligo- and polyenaminones with M w ∼ 3000 Da were prepared in excellent yields by amino–enaminone 'click' polymerisation of 1, 3- and 1, 4-bis[3-(dimethylamino)acryloyl]arenes with 1, 3- and 1, 4-phenylenediamine. The obtained oligomers and polymers were depolymerised quantitatively to the starting bis-enaminones and diamines by treatment with excess dimethylamine in ethanol at 50 °C. This simple polymerisation/depolymerisation method allows for a closed-loop recycling of polyenaminone-based materials. UV light absorbance at wavelengths below 470 nm indicates promising optical properties of these polymers.